The effect of chronic doxorubicin treatment on mitogen-activated protein kinases and heat stress proteins in rat hearts - Šimončíková, P; Ravingerová, T; Barančík, M (Physiological research, 2008)
The study has been designed to characterize protein systems involved in the responses of rat hearts to chronic doxorubicin (DOX) treatment. We investigated the influence of DOX on cardiac function, mitogen-activated protein kinases (MAPKs) and heat stress proteins (HSPs). Doxorubicin was administered to rats by intraperitoneal injections over a period of 6 weeks. In control and DOX-treated hearts exposed to 20 min global ischemia and 40 min reperfusion the recovery of contractile function after ischemia/reperfusion (I/R) was determined. The levels and phosphorylation state of proteins in tissue samples were analyzed using specific antibodies. We found an activation of extracellular signal-regulated kinases (ERKs) in rat hearts exposed to DOX treatment and better recovery of contractile function after I/R. Analysis of HSPs showed that DOX induced up-regulation of the levels of HSP60 and down-regulation of HSP70 levels. The levels and/or specific phosphorylation of other studied proteins (p38-MAPK, HSP27, HSP90) were not influenced by DOX. The results point to the possible role of ERKs and some HSPs in mechanisms underlying the response of rat hearts to chronic DOX treatment.
Keywords: Animals; nemoci srdce; reperfuzní poškození myokardu; Phosphorylation; HSP27 Heat-Shock Proteins; Extracellular Signal-Regulated MAP Kinases; kontrakce myokardu; protinádorová antibiotika; zvířata; Disease Models, Animal; HSP90 Heat-Shock Proteins; chaperon hsp60; Myocardial Reperfusion Injury; extracelulárním signálem regulované MAP kinasy; Doxorubicin; myokard; Myocardial Contraction; proteiny tepelného šoku HSP70; Chaperonin 60; nádorové proteiny; Heart Diseases; Myocardium; proteiny tepelného šoku HSP90; mitogenem aktivované proteinkinasy p38; Rats; p38 Mitogen-Activated Protein Kinases; proteiny tepelného šoku HSP27; Male; Neoplasm Proteins; HSP70 Heat-Shock Proteins; krysa rodu Rattus; doxorubicin; Heat-Shock Proteins; mužské pohlaví; Antibiotics, Antineoplastic; modely nemocí na zvířatech; fosforylace; proteiny teplotního šoku